Short Communication: Bacillus endolithicus and Bacillus paramycoides: New isolates from housefly Musca domestica in Saudi Arabia - dina Ezzat Elghwas; ABIR S. AL-NASSER; AISHA A. AL-SHEIKHY (Society for Indonesian Biodiversity, 2021)
Abstract. El-Ghwas DE, Al-Nasser AS, Al-Sheikhy AA. 2021. Short Communication: Bacillus endolithicus and Bacillus paramycoides: New Isolates from housefly Musca domestica in Saudi Arabia. Biodiversitas 22: 4209-4214. Housefly Musca domestica Linnaeus is a common insect widely distributed all over the world. It is one of the domestic insects found associated with humans and animals. The present study investigated the bacterial diversity associated with Musca domestica samples collected from different places such as food courts and trash cans near fast-food restaurants in Makkah Province from October 2019 to December 2019. Eighteen pure isolates of bacterial strains were isolated and identified by Gram staining. Most of the bacterial isolates were Gram-positive except for two species, which were Gram-negative. The VITEK system was used to identify randomly isolate no. 5, 7, 17, 18, and 29. The results revealed that they belonged to the genus Bacillus sp., Staphylococcus sp., Pseudomonas sp., and Micrococcus sp. respectively. Due to the most isolated strains were Bacillus sp., so 16S RNA was used to genetically identify novel isolated strains 5 and 7. Isolate no. 5 showed the highest similarity (99 %) with Bacillus endolithicus, and isolate no. 7 showed the highest similarity (99 %) with Bacillus paramycoides. This is the first record of Bacillus endolithicus and Bacillus paramycoides to be isolated from the house fly Musca domestica L.